Computer Simulations of Contact Forces for Airbags with Different Folding Patterns During Deployment Phase - King H. Yang; Yun-Qiang Li; Danyu Sun (Shock and Vibration)
An explicit finite element method was used to study the neck load and the contact force between an occupant and an airbag during an out-of-position frontal automobile crash. Two different folding patterns and two different mounting angles of the airbag were simulated. For the four cases simulated, the occupant’s neck axial force ranged from 156 to 376% of the data obtained from in-position sled tests using the Hybrid III dummy. The neck shear force ranged from 87 to 229% and the neck flexion moment ranged from 68 to 127% of in-position experimental results. In both 300 mounting angle simulations, the neck axial forces were higher than that of the two simulations with 00 mounting angles, but the trend for the neck shear force was the opposite. Although the kinematics of the model appear reasonable, the numbers generated by the model must be reviewed with great caution because the model has not been fully validated.